Categories of lattices, and their global structure in terms of almost split sequences - Rump, W. (Algebra and Discrete Mathematics, 2004)
A major part of Iyama’s characterization of
Auslander-Reiten quivers of representation-finite orders Λ consists
of an induction via rejective subcategories of Λ-lattices, which
amounts to a resolution of Λ as an isolated singularity. Despite
of its useful applications (proof of Solomon’s second conjecture
and the finiteness of representation dimension of any artinian algebra), rejective induction cannot be generalized to higher dimensional Cohen-Macaulay orders Λ. Our previous characterization
of finite Auslander-Reiten quivers of Λ in terms of additive functions [22] was proved by means of L-functors, but we still had to
rely on rejective induction. In the present article, this dependence
will be eliminated.